PENGARUH MEDIA HOUSE COUNT TERHADAP KEMAMPUAN BERHITUNG PADA ANAK USIA 5–6 TAHUN DI PAUD AZKIA KECAMATAN TEMBILAHAN KABUPATEN INDRAGIRI HILIR - Atmeirida, Nofia Rahyefi; Chairilsyah, Daviq Chairilsyah; Solfiah, Yeni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the results of field observations on the numeracy skills of students has not developed optimally. So it is necessary to apply the House Count media. The purpose of this study was to examine the effect of using House Count media on the numeracy skills of children aged 5-6 years. This research was conducted at PAUD Azkia of Tembilahan sub-district Indragiri Hilir district during January 2019 to April 2019 for observation and research. The research used experimental method with one group pre-test post-test design with 15 samples. The data collection technique used in this research is using observation sheet the numeracy skills of student. Data analysis technique using t-test by using SPSS program ver 20. From result of data analysis obtained tcount equal to 27,938 bigger than t table = 2,145 with sig 0.000 <0.05. It can be concluded that there are differences in the numeracy skills significantly before and after the application of the House Count media. Based on hypothesis test results obtained there is the effect of use House Count media to the numeracy skills of children aged 5-6 years in PAUD Azkia of Tembilahan sub-district Indragiri Hilir district of 70% .Key Words: House Count, Numeracy Skills